The Old Testament "Apocrypha" in Jerome's Canonical Theory - Gallagher, Edmon L. (Journal of early Christian studies, 2012)
In his preface to Samuel and Kings (the Prologus Galeatus), Jerome sets forth a theory of the Old Testament canon that allows for no room between the canonical books and the apocrypha. However, Jerome elsewhere maintained a more neutral or even positive view of some of the non-canonical books, even accepting their use within the ecclesiastical liturgy. Jerome's seemingly inconsistent attitude toward some books he classifies as "apocrypha" has led scholars to posit a development in Jerome's canonical theory, such that his earlier position was accepting of books that he later excluded, and to suppose that Jerome's use of the word "apocrypha" in the Prologus Galeatus relied on a neutral definition of the term. This paper examines the evidence for these claims and finds them wanting. While Jerome consistently regarded the books labeled "apocrypha" in the Prologus Galeatus as outside the canon, he chose to propagate an especially harsh judgment against these books especially in this preface. The confusion arising from Jerome's comments may be explained as a consequence of a multi-faceted plan to realign the church's Old Testament with the Hebrew Bible, a plan that Jerome articulates only partially on any given occasion.